Handbook of research on technology integration in the global world - Idemudia, Efosa C. (Efosa Carroll), 1970- (Information Science Reference, an imprint of IGI Global, 2019)
"This book addresses the design and implementation of e-collaboration technologies, assesses its behavioral impact on individuals and groups, and presents theoretical considerations on links between the use of e-collaboration technologies and behavioral patterns. It also covers the wide facets of e-adoption ranging from infrastructural research to socio-economic impact"--